Respostas
respondido por:
9
lembre-se: (a+b)^2 = a^2 + 2ab + b^2
a) 9x^2 + 6x + 1
b) 4a^2 + 20a + 25
c) a^2 + 4ab × 4b^2
a) 9x^2 + 6x + 1
b) 4a^2 + 20a + 25
c) a^2 + 4ab × 4b^2
Gabss100:
tem como fazer sem ser direto? pq olhe kkk
respondido por:
8
a) (3x + 1)^2 =
(3x)^2 + 2.3x.1 + 1^2 =
9x^2 + 6x + 1
b) (2a + 5)^2 =
(2a)^2 + 2.2a.5 + 5^2 =
4a^2 + 20a + 25
c) (a + 2b)^2 =
a^2 + 2.a.2b + (2b)^2 =
a^2 + 4ab + 4b^2
Espero ter ajudado!
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás